For In-Pipe Inspection Platform - Tan, Wei Jun (Universiti Sains Malaysia, 2017)
Culvert is a special concrete pipe which is generally utilized as a cross channel for ditch alleviation and to pass water under the road. Inspection for corrosion or damage of the culvert is an important aspect of safety and using an in-pipe inspection robot is the most reliable and convenient way of doing this. It is necessary to obtain and predict the location of the damaged area and have a real time visualization to achieve this capability. This project is aimed at presenting the design, development and implementation of a localization and visualization system for culvert inspection platform. In this project, a system is introduced to acquire and display real-time video streaming so it can be used to determine the condition of large diameter culvert (180mm-450mm). An inspection camera together with a headlight are mounted on a swivel head attached to a body (robot) which has a wheel to enable it to move forward or backward. IMU module is attached to obtain several data. Web browser is the platform to visualize and control the movement of robot.